Nursing diagnoses for clients hospitalized in an infectious disease clinic - Andrade, Lidiane Lima de; Nóbrega, Maria Miriam Lima da; Freire, Maria Eliane Moreira; Nóbrega, Renata Valeria (Revista da Escola de Enfermagem da USP, 2013)
The aim of this exploratory descriptive study was to create nursing diagnosis statements for hospitalized clients based on the Database of Special Nursing Language Terms of the Infectious Diseases Clinic of a teaching hospital and on the ICNP®. Further, we aimed to validate the diagnosis statements with the participation of clinical nurses and nursing teachers who worked at the clinic. Eighty-eight nursing diagnosis statements were constructed. However, only those that achieved a correlation index (CI) ≥ 0.80, as determined by the experts participating in the study, were validated, resulting in seventy diagnosis statements. The study results showed that the aims were achieved, and the statements will facilitate communication processes among nursing professionals. Furthermore, they will ensure that care is guided by methodological principles, thus providing client care with greater resolvability power.